Non-Classic Legal Thought in the Post-Soviet Space - Alexey V. Stovba (Антиномии, 2021)
The following article is about the main trends of understanding of law in the former Soviet Union. These trends are the so-called “classical” and “nonclassical” (“post-classical”) understanding of law; both find itself in the mutual debates between one another. At the same time, non-classical legal philosophy in the former Soviet Union doesn’t take the ideas from the Western thought uncritically, but tries to elaborate its own view on the legal field. The specificity of that view may be characterized by the concept of “dynamic understanding of law”. The similar concept is the common title for the wide range of the doctrines, which were elaborated in Russia, Ukraine and Belorussia on the edge of the centuries. These are, for example, phenomenological-communicative approach of A.V. Polyakov, doctrine of the legal dialogue of I.L. Chestnov, temporal-ontological philosophy of law (A.V. Stovba), the conception of legal reality (S.I. Maksymov) and so on. It’s worth to stress that all the abovementioned legal doctrines are independent from one another and original. But at the same time, they have common features, which allow us to significate it under the common title “dynamic understanding of law”. The similar features are the following: negative position towards the reification of law; towards the attempts to consider law in the frame of subject-object relations; towards the representation of law as the static, continual “Ought”, which regulates its object – “Is” – from the “secure” transcendental distance. Instead, the abovementioned legal philosophers propose to consider law as dynamic (discrete and reproduced) in its core, which originally has social roots and character. At the same time, despite the originality of the similar views to the law, we can find its historical parallels in the national legal discourse, as well in the foreign legal philosophy. The conclusion is made that the dynamic understanding of law is the adequate conceptual approach to the general reasoning of the legal essence.